Answer:
hence g(x) is increasing at point x= 3+14i,3-14i
Step-by-step explanation:
given, g(x)=x^3-(8+1)x^2-4(9+2)x+5x2-1
g(x)=x^3-9x^2-44x+10x-1
g(x)=x^3-9x^2-34x-1
=3x^2-18x-34
for increasing and decreasing function,
3x^2-18x-34=0
x=3+14i
0
x=3-14i
0
hence g(x) is increasing at point x= 3+14i,3-14i answer
Answer:
35 is greater than the other options.Step-by-step explanation:
Answer: y = -5; x = -2
Step-by-step explanation:
- 5y – 10x=45
- 3y + 10x = -5
Combining both equations
-8y = 40
y= 40/ -8
y = -5
Substitute y = -5 into any of the equations to get the value of x
-5 (-5) - 10x = 45
25 -10× = 45
-10x =45 -25
-10× = 20
Divide both sides by -10
x = -2
Mark as brainliest please
Answer:
- reflection over the x-axis
- translate right 2 units
- translate down 3 units
Step-by-step explanation:
Horizontal translation of the graph of a function is accomplished by replacing x with (x-h) for translation h units to the right. Vertical translation of the graph is accomplished by adding the amount of translation to the function value: f(x)+k translates the graph k units upward.
Reflection of a function over the x-axis is accomplished by changing the sign of every function value: -f(x).
<h3>Application</h3>
We observe that f(x) has been transformed by ...
- multiplying by -1 to get -f(x)
- replacing x with (x -2) to get -f(x -2)
- adding -3 to the function value to get -f(x -2) -3
The effect of these transformations is (correspondingly) ...
- reflection over the x-axis
- translate right 2 units
- translate down 3 units
__
The attached graph shows a function f(x) (red) and the transformed function (blue).